MODELING THE FORMATION OF POLYLACTIDE MICROSPHERES - Indra Gunawan; Aloma K. K.; Sudirman Sudirman (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2007)
MODELING THE FORMATION OF POLYLACTIDE MICROSPHERES. Biodegradable polylactide microspheres have been developed from a dispersion solution of polylactide in chloroform with polyvinyl alcohol in water. The present paper focuses on developing an understanding of microspheres formation through simple dimensional analysis and principle of system similarity for microstructure observation of microsphere diameter formed. Theoretical correlation between microspheres diameter and agitation rate was derived with the concept of similarity. While the empirical correlation between Weber (We) number and microspheres diameter was derived from dimensional analysis of variables that is useful for prediction of microspheres diameter to support Holmium powder. The empiric equation of the microspheres diameter forming as a function of essential process parameters is: ln (dm/dp) = -4.81 + 0.593 ln We.